Action and inertia in the study of hyphal growth. (September 2022) - Money, Nicholas P.
Abstract: Hyphae are microscopic filaments that elongate and branch to create networks of interconnected tubes. Understanding how they work remains a formidable challenge in experimental mycology. Important advances in hyphal research in the 20 th century came from electron microscopy, which revealed clusters of cytoplasmic vesicles in the cell apex, and biochemical studies that identified the cell wall materials that are assembled at the tip. Early genetic experiments on hyphae based on mutant analysis were disappointing and provided little information on the relationship between genotype and phenotype. Progress has come more recently, in the first decades of this century, by combining the techniques of molecular genetics with modern imaging methods. Live-cell imaging has allowed us to study the dynamics of cell components in strains of fungi engineered with plasmids encoding proteins fused to fluorescent probes. This technology has provided significant insights on the growth process and yet the fundamentals of hyphal growth remain elusive. Highlights: Research on hyphal growth has advanced through live-cell imaging Tracking the movement of proteins attached to fluorescent reporters has become a particularly valuable experimental tool Many fundamental questions about the growth of fungal hyphae remain unanswered